Effect of Bifidobacterium Probiotic in the Treatment of Giardiasis Infection in Mice (Baghdad Science Journal, 2019)
Metronidazole therapy is recommended in the treatment of giardiasis,athough some clinical reports mention the resistance to this drug from many pathogens. Many studies were applied to show the effect of probiotic to prevent or to heal diseases of gastrointestine, but only few is known about probiotic activity against infections of protozoa. This study aims to evaluate the efficiency of Bifidobacterium against infection with Giardia lamblia in experimental mice. It was found that daily application of viable Bifidobacterium cells with a single dose (0.1ml∕mice∕day) significantly reduced the shedding of Giardia lamblia parasite cysts in feces, and infection completely disappeared at the day (15th) post inoculation with this probiotic. Also, it was noticed that Giardia cysts were reduced in the group treated with metronidazole, and infection cured at day (17th) from treatment, while the control group showed shedding cysts of this parasite. Histopathologically, the effect of Bifidobacterium in vivo by gut cells modulation prevents the colonization of Giardia, leading to reduce the infection with this parasite.